Architectural history education: students’ perception on mobile augmented reality learning experience - Sanusi, Aliyah Nur Zafirah; Abdullah, Fadzidah; Kassim, Mohd Hisyammudin; Tidjani, Abhari Ahmat (American Scientific Publishers, 2018)
Learning Architectural History in architecture schools remains as a challenge to many students in the built environment institutions. Historical buildings information can be very complicated and complex, that make learning considerably difficult, especially when there are too many variations of building shapes, forms, and treatments. The implementation of traditional learning and teaching method, solely via lecture that is currently still in practice, may have contributed to students’ difficulty to understand and experience historical buildings to the optimum level. As Mobile Augmented Reality (MAR) application's popularity is increasing in the educational field, it inspires researchers to evaluate students’ perception on MAR usage for the architectural history education. Hence, this research aims to explore the usage of Mobile Augmented Reality (MAR) application as a new innovative method for students to learn architectural history intuitively and interestingly. The research has two objectives; firstly, to investigate the MAR current practice on architectural history education, and secondly, to evaluate students’ perception of MAR in assisting students’ learning experience. The researchers adopt mixed methods approaches, consisting of literature reviews, and survey questionnaires. As a conclusion, MAR promises a new wave of the learning experience for students, which provides flexible and intuitive learning activities to them.